2006
DOI: 10.1213/01.ane.0000184257.54917.99
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Sevoflurane and Propofol on QT Interval and Heterologously Expressed Human Ether-A-Go-Go Related Gene Currents in Xenopus Oocytes

Abstract: Sevoflurane can induce prolongation of the cardiac QT interval by inhibiting the repolarization phase of the action potential. This may occur as a result of inhibition of the human ether-a-go-go related gene (HERG) channel. To clarify the mechanisms of anesthetics on HERG channels, we monitored the electrocardiogram and measured QT intervals in the guinea pig in the presence of sevoflurane and propofol. Sevoflurane (1%-4%) prolonged QTc dose-dependently (7.5%-21.2%), but propofol did not affect it. Furthermore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 20 publications
1
29
0
Order By: Relevance
“…Our experiments with the use of E-4031 and chromanol 293B, which selectively block I Kr and I Ks , respectively, suggest that propofol served as a selective blocker of I Ks . In line with this, our recent study has shown that propofol has a much less pronounced effect on the HERG channel that encodes I Kr (28). Furthermore, Heath and Terrar (24) have indicated that plasma levels of propofol during induction and maintenance of anesthesia are in the range observed to reduce cardiac I Ks .…”
Section: +supporting
confidence: 52%
See 1 more Smart Citation
“…Our experiments with the use of E-4031 and chromanol 293B, which selectively block I Kr and I Ks , respectively, suggest that propofol served as a selective blocker of I Ks . In line with this, our recent study has shown that propofol has a much less pronounced effect on the HERG channel that encodes I Kr (28). Furthermore, Heath and Terrar (24) have indicated that plasma levels of propofol during induction and maintenance of anesthesia are in the range observed to reduce cardiac I Ks .…”
Section: +supporting
confidence: 52%
“…Moreover, propofol is known to modulate several ionic currents other than I Ca (24 -28). The inhibitory effects of propofol on cardiac Na + current (I Na ), transient outward K + current (I to ), and delayed rectifier K + current (I K ) have been demonstrated (24,25,28). Propofol also inhibits the current generated by hyperpolarization-activated cyclic nucleotide-gated channels at clinically relevant concentrations (27).…”
Section: Introductionmentioning
confidence: 99%
“…Repolarization of the ventricular myocytes depends mainly on the sum of the outward potassium currents, particularly on the delayed rectifier potassium current, which is composed of rapidly (Ikr) and slowly (Iks) activating components, and inward calcium current. Propofol has no effect on the human ether-a-go-go related gene (HERG) outward current expressed in Xenopus oocytes, corresponding to Ikr, 12) though it blocks the min K current expressed in Xenopus oocytes, which corresponds to Iks. 13) On the other hand, propofol directly blocks the L-type calcium channel in guinea pig myocytes, and tends to shorten the action potential duration.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we used vecuronium for neuromuscular relaxation and tracheal intubation as it has been found to have no effect on the QTc interval [2,8,18]. However, it has been reported that there is no dose-dependency in the dose-response relationship between propofol and the QTc interval [20], and in consideration of tracheal intubation, the effect-site concentration was set at 5 lg.ml )1 in this study.…”
Section: 贸 2008 the Authorsmentioning
confidence: 99%